2022
DOI: 10.1186/s12913-022-07958-8
|View full text |Cite
|
Sign up to set email alerts
|

Peer support in an outpatient clinic for people living with human immunodeficiency virus: a qualitative study of service users’ experiences

Abstract: Background Although human immunodeficiency virus (HIV) has become a manageable condition with increasing life expectancy, people living with HIV (PLHIV) are still often isolated from society due to stigma and discrimination. Peer support provides one avenue for increased social support. Given the limited research on peer support from the perspective of PLHIV, this study explored their experiences of peer support organised by healthcare professionals in an outpatient clinical setting. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
(53 reference statements)
0
5
1
Order By: Relevance
“…Therefore, peer volunteers are important resources for providing comprehensive support for PLHIV beyond medical professionals. Many qualitative studies have shown the great necessity of emotional support 51 53–55 69. However, we found only weak evidence that peer support has intervention effects on psychological outcomes.…”
Section: Discussioncontrasting
confidence: 64%
See 4 more Smart Citations
“…Therefore, peer volunteers are important resources for providing comprehensive support for PLHIV beyond medical professionals. Many qualitative studies have shown the great necessity of emotional support 51 53–55 69. However, we found only weak evidence that peer support has intervention effects on psychological outcomes.…”
Section: Discussioncontrasting
confidence: 64%
“… 56 76 81 82 Second, access to a safe place reassures both PLHIV and peer volunteers of privacy exposure concerns. 53 Third, more communication between peer volunteers and medical staff is necessary to reduce the information gap and to better integrate volunteers into the clinical setting. 52 55 70 83 Fourth, the context should provide continuous training for peer volunteers to meet their self-growth needs and be more effective in their role as peer supporters.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations